Comparison of Cr(VI) adsorption and photocatalytic reduction efficiency using leonardite powder. (August 2022) - Arslan, Hudaverdi; Eskikaya, Ozan; Bilici, Zeynep; Dizge, Nadir; Balakrishnan, Deepanraj
Abstract: It is very important to treat Cr(VI) from the aquatic environment due to its toxic and harmful effects. Conventional treatment methodology involving biological pathways is generally ineffective for wastewater containing Cr(VI). Therefore, it is necessary to develop environmentally friendly and economical methods to remove Cr(VI) from the aquatic environment. In this study, leonardite, which is a natural mineral that has no harmful effects on the environment, was used for Cr(VI) removal. Leonardite was used in both adsorption and photocatalytic treatment systems by only pulverizing without any chemical treatment. Characterizations of leonardite were obtained using X-ray fluorescence (XRF), fouirer transform infrared spektrofotometre (FTIR), scanning electron microscopy (SEM) with energy dispersive X-ray analysis (EDX) analyses methods. The effects of solution pH (2-10), particle size (45–300 μm), adsorbent dose (0.25–3 g/L), and initial concentration (10–30 mg/L) on Cr(VI) removal efficiency were investigated in both adsorption and photocatalytic experiments. In the adsorption process, a complete removal efficiency (100%) was obtained for 3 g/L of adsorbent dose with an initial Cr(VI) concentration of 10 mg/L at pH 2 for 2 h. In the photocatalytic process, 100% removal efficiency of Cr(VI) was obtained when four times less adsorbent dosage was used under the same conditions. In addition, the reuse of leonardite powder was also investigated under optimum experimental conditions. Leonardite powder preserved approximately 70% of its activity in the photocatalytic process while it lost 50% of its activity after 5 reuses in adsorption process. Graphical abstract: Image 1 Highlights: Leonardite powder was used for adsorption and photocatalytic reduction of Cr(VI). 100% adsorption removal efficiency was obtained for 3 g/L of dose with an initial Cr(VI) concentration of 10 mg/L at pH 2. 100% photocatalytic reduction efficiency was obtained for 0.75 g/L of dose at the same conditions of adsorption process. Leonardite powder preserved 70% of its activity in the photocatalytic process after 5 reuses.